PROGRAM RPJPD DALAM MEWUJUDKAN KOTA SAMARINDA SEBAGAI KOTA METROPOLITAN - Mahfudlah Fajrie; Abdul Wahab; Durrotul Maghfiroh (An-Nida : Jurnal Komunikasi Islam, 2021)
The RPJPD program in realizing the city of Samarinda as a metropolitan city is the third stage of long-term regional development by the mandate of regional regulation no.4 of 2005 concerning the regional long-term development plan (RPJPD) of Samarinda city for 2005-2025. The VISION of this programming in the 2016-2021 period is to realize Samarinda as a competitive and environmentally friendly metropolitan city. The relationship between elements of the VISION of the city of Samarinda with sustainable development is seen from three important aspects, namely social aspects, economic aspects, and environmental aspects. The MISSION and nine priority agendas that emphasize governance, strengthen Samarinda city finances, create a livable city space, strengthen the service and trade sector as a leading sector, create Samarinda city people who are characterized, healthy, smart, and have national competitiveness and international life and create a harmonious, cultural, and religious climate of life for the people of Samarinda City. Keywords: Development, Metropolitan City, Long Term Program Progaram RPJPD dalam mewujudkan kota Samarinda sebagai kota metropolitan merupakan tahap ketiga pembangunan jangka panjang daerah yang sesuai dengan amanat peraturan daerah no.4 tahun 2005 tentang rencana pembangunan jangka panjang daerah (RPJPD) kota Samarinda tahun 2005-2025. VISI dari pemrograman ini dalam periode 2016-2021 adalah untuk mewujudkan kota Samarinda sebagai kota metropolitan yang berdaya saing dan berwawasan lingkungan. Keterkaitan elemen VISI kota Samarinda dengan pembangunan berkelanjutan ini dilihat dari tiga aspek penting, yaitu aspek sosial, aspek ekonomi dan aspek lingkungan. Adapun MISI dan sembilan agenda prioritas yang menekankan pada tata kelola pemerintahan, memantapkan keuangan kota Samarinda, mewujudkan ruang kota yang layak huni, memantapkan sektor jasa dan perdangan sebagai sektor unggulan, mewujudkan masyarakat kota Samarinda yang berkarakter, sehat, cerdas, serta berdaya saing nasional dan internasional dan mewujudkan iklim kehidupan masyarakat kota Samarinda yang harmoni, berbudaya, dan religius. Kata Kunci : Pembangunan, Kota Metropolitan, Program Jangka Panjang